Dkicen Catering Booking and Recommendation System - Mustapa, Nur Aimi; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2025)
Dkicen Catering, based in Klang, Selangor, faces operational challenges due to reliance on manual communication channels, resulting in miscommunication and order issues. To address this, the study aims to design and implement an online ordering system. Objectives include enhancing customer satisfaction, streamlining order processing, and generating monthly reports for financial monitoring. The project involved three users which are administrator , staff and customers. The approach is object-oriented for developing the system. The expected outcome is the Dkicen Catering Booking and Recommendation System, improving efficiency, reducing errors, and benefiting both the company and customers. This project signifies a transformative step towards efficient, customer-centric order management. In conclusion, the developed system could benefit the catering company in managing orders from customers.